Pertempuran Surabaya 10 November 1945: Titik balik dalam sejarah kemerdekaan Indonesia - Maulana, Much. Rizki (Maliki Interdisciplinary Journal, 2024)
The Battle of Surabaya on 10 November 1945 was an important turning point in the history of Indonesian independence, reflecting the strong spirit of struggle and determination to defend the country's sovereignty. In the context of post-World War II global history, this event became an international highlight, illustrating the new power dynamics in Southeast Asia. This study will combine various historical sources, academic literature, and related documentation to provide an in-depth analysis of the Battle of Surabaya. By utilizing historical journals, recent history books, and relevant literature studies, this article will go beyond a mere chronology of events. We will explore the military strategies implemented, the political decisions that influenced the battle, the iconic role of figures such as Bung Tomo, and their far-reaching impact on the development of Indonesian nationalism. It is hoped that with this comprehensive interdisciplinary approach, this article will bring a deeper understanding of the urgency and relevance of the Battle of Surabaya in the context of Indonesian history. The involvement of journal and literary sources will enrich the analysis and provide a solid foundation for exploring key aspects of this historical event.